Some zerconid mites (Acari: Mesostigmata: Zerconidae) from Kosovo (Serbia-Montenegro) with description of Zercon kosovina sp. nov. - Kontschán, Jenõ (Zootaxa, 2006)
Three Zerconid mite species were collected in Kosovo (Serbia and Montenegro). Two of them, Zercon moravicus Halaškova, 1970 and Prozercon fimbriatus (C. L. Koch, 1839), are known species, but the third, Zercon kosovina sp. nov., proved to be new to science.